Analisis Faktor-Faktor yang Mempengaruhi Struktur Utang Perusahaan Go Public yang Terdaftar di Bursa Efek Jakarta - Shiddiq Nur Rahardjo; Berty Hartatiningrum (Jurnal Akuntansi dan Bisnis, 2006)
Liabilities is one of company’s sources to fill its fund needs. According to the sources, liability (debt) divided into public debt and private debt. This research was conducted to analyze the influence of variables such as debt maturity, leverage, firm size, liquidity, and dividend payout ratio to the the debt structure of the go-public companies listed in Jakarta Stock Exchange. Besides, this research is also conducted to know the proportion of company’s debt structure. In conducting this research, the authors used purposive sampling method to collect the data with some criteria as follows: (1) Issuing bond at the year of 2000-2004 (2) Not including banking companys (3) Issuing the financial statement in the period of its bond’s issued. The selected samples are 50 companies. The authors used multiple linier regressions as the method of data analysis. Partially and simultanly, to determine the influence of independent variables, the writer used t-test and F-test with level of significance 5%. The result showed that there are three independent variables that proven has influence partially to the company’s debt structure; firm size, liquidity, and dividend payout ratio. The result of F-test showed that all of the independent variables used in this research have significance influence to the company’s debt structure.